EFFECTIVE WAYS OF TEACHING ENGLISH AS FOREIGN LANGUAGE TO YOUNG LEARNERS - Turakulova Nilufar Mamaraim's daughter (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
THis article aims to find out the understanding and age-appropriate guides for teaching English as an advanced languaging to the young generation,especially,students. In addition,how to teach the young generation to learn and master the language in a way that is convinient for them. It is reflected that it is important to create atmosphere and conditions. This research shows that different technological applications like songs,stories and games are important in the language learning process. Additionally,research highlighting the importance of language teaching methods and lesson plans for young learners.